2020
DOI: 10.1016/j.ijpddr.2020.10.007
|View full text |Cite
|
Sign up to set email alerts
|

Rapid determination of nematode cell and organ susceptibility to toxic treatments

Abstract: In research focused on the intestine of parasitic nematodes, we recently identified small molecule inhibitors toxic to intestinal cells of larval Ascaris suum (nematode intestinal toxins/toxicants; “NITs”). Some NITs had anthelmintic activity across the phylogenetic diversity of the Nematoda. The whole-worm motility inhibition assay quantified anthelmintic activity, but worm responses to NITs in relation to pathology or affected molecular pathways was not acquired. In this study we exten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(23 citation statements)
references
References 71 publications
1
22
0
Order By: Relevance
“…Results from a PI-based cell death assay and GRPs can augment insights provided by whole-worm motility inhibition assays that are commonly used to evaluate effects of drugs and drug-like compounds on parasitic nematodes. The rapid resolution of individual cells and organs affected by these treatments in live worms greatly enhances details of likely relevance to the anthelmintic effects at play, as was demonstrated in our previous studies in the nematode clade III parasite, A. suum [ 3 , 4 ]. In this investigation, we explored the utility of the overall experimental approach to another parasitic species, H. contortus , a clade V parasite.…”
Section: Resultsmentioning
confidence: 96%
See 4 more Smart Citations
“…Results from a PI-based cell death assay and GRPs can augment insights provided by whole-worm motility inhibition assays that are commonly used to evaluate effects of drugs and drug-like compounds on parasitic nematodes. The rapid resolution of individual cells and organs affected by these treatments in live worms greatly enhances details of likely relevance to the anthelmintic effects at play, as was demonstrated in our previous studies in the nematode clade III parasite, A. suum [ 3 , 4 ]. In this investigation, we explored the utility of the overall experimental approach to another parasitic species, H. contortus , a clade V parasite.…”
Section: Resultsmentioning
confidence: 96%
“…In past research, the effects of six nematode intestinal toxins/toxicants (NITs) were reported for A. suum L3 and L4 larvae (staurosporine, ruxolitinib, leflunomide, sunitinib, alvocidib, and CID1067700) [ 3 , 4 ]. A seventh NIT not previously reported (p38 MAP kinase inhibitor IV, also known as MT4) was identified through the same de novo process as in Jasmer et al, 2020 [ 3 ] and is a prospective inhibitor of p38 MAP kinases.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations